Farmers’ eviction in Perak, Malaysia: Linking social theories with food security - Raja Mazlan , Raja Nur Hidayah; Abdul Haziz , Hazliza; Noor Nirwandy, (Journal of Islamic, Social, Economics and Development, 2024)
The paper examines the eviction of traditional farmers in Perak, Malaysia in the case occurs in the end of 2023 and ongoing early 2024, through the lens of social theories and their implications for human and food security. Traditional farmers, who rely on agricultural methods passed down through generations, are being unjustly evicted in the name of development without appropriate measures or consideration by the law or the government. To observe this, concepts like biopower, and how governments exercise it, with the clashes of conflict theory, systems theory, and human rights theory to contextualize the complex dynamics at play. The authors argue that integrating social theories with human and food security offers a comprehensive framework for understanding and addressing the availability, access, and utilization of food in society, on top of highlighting the traditional farmer’s stand on their way of life for generations. They highlight how structural inequalities, and power dynamics and compare it with the current global and existing situations contribute to food insecurity, as seen in examples like the situation in other parts of the world mainly observed in Congo, Philippines and Palestine. The paper emphasizes the importance of the mentioned above social theories in ensuring problems like outdated land law and transparency in the land law Malaysia as the problem could actually help the empowerment of the local producers and sustainability as key dimensions of food security and human security in Malaysia. In the context of communication and media warfare, the authors link social theories to the representation of the farmers' eviction, underscoring how media narratives and mainstream information about laws can amplify or marginalize voices and influence public opinion and policy responses. The paper concludes by stressing the need for policies and communication strategies that uphold the rights and dignity of vulnerable populations like the evicted farmers, fostering an equitable dialogue that supports human security principles.